Associations between dietary microbe intake and mortality risk in individuals with sleep disorders: Evidence from NHANES. - Xuanchun Huang; Lanshuo Hu; Ruikang Liu; Jun Li; Tiantian Xue (PLoS ONE, 2025)
Objective To investigate the association between dietary microbial intake, sleep patterns, and all-cause and cardiovascular mortality among U.S. adults. Methods This study is conducted using data from the 2005-2014 National Health and Nutrition Examination Survey (NHANES). Kaplan-Meier curves are used to preliminarily explore the relationship between dietary microbial intake, sleep disorders, and all-cause and cardiovascular mortality in the population. The Cox proportional hazards model is applied for both individual and combined analyses to examine the relationship between dietary microbial intake, sleep disorders, and mortality risk, with subgroup and sensitivity analyses performed to assess model stability. Results This study included 21,233 participants, among whom 2,814 all-cause deaths and 877 cardiovascular deaths were documented. Kaplan-Meier survival analysis revealed a significant association between low dietary microbial intake or sleep disorders and elevated mortality. Cox proportional hazards modeling showed that, among individuals with sleep disorders, those with moderate dietary microbe intake had a lower mortality hazard ratio compared to those with low intake. Conversely, the combination of low dietary microbe intake and sleep disorders was associated with the highest all-cause and cardiovascular mortality. Subgroup and sensitivity analyses demonstrated consistent associations across prespecified strata, with the inverse relationship between dietary live microbe intake and sleep disorder-related mortality remaining robust after adjustment for confounders. Conclusion Low dietary microbial intake and sleep disorders were independently and jointly associated with higher rates of all-cause and cardiovascular mortality in population. The observed inverse association between higher dietary microbial intake and mortality outcomes, particularly among individuals with sleep disorders, suggests a potential protective trend.